Empowering students' critical thinking skills using problem-based learning - Sartika, Weni; Rahman, Sari Rahayu; Irfan, M. (Inornatus: Biology Education Journal, 2023)
This research aims to ascertain how students' critical thinking skills change after being exposed to Problem-Based Learning (PBL). This study employs a quantitative methodology using quasi-experiments. Non-equivalent control groups were employed in this study. The population included 246 students from seven different classes at IPA SMA Negeri 1 Mamasa, who were all in grade XI. This research used a purposive sample of 36 students from the PBL class and 36 students from the control class. The t-test and the Mann-Whitney test were used to analyze the data in this investigation. The t-test results showed that the students' pretest was different (sig. <0.05), so the posttest t-test also showed a difference (sig. <0.05). The Mann-Whitney N-gain test was used to find out whether PBL had a statistically significant impact. The Mann-Whitney test found that the students' critical thinking had improved if the significance level (Sig. of N-gain) was less than 0.05. This study provides evidence that PBL may improve students' critical skills.